2022
DOI: 10.1111/acer.14777
|View full text |Cite
|
Sign up to set email alerts
|

A review of alcohol–pathogen interactions: New insights into combined disease pathomechanisms

Abstract: Progression of chronic infections to end‐stage diseases and poor treatment results are frequently associated with alcohol abuse. Alcohol metabolism suppresses innate and adaptive immunity leading to increased viral load and its spread. In case of hepatotropic infections, viruses accelerate alcohol‐induced hepatitis and liver fibrosis, thereby promoting end‐stage outcomes, including cirrhosis and hepatocellular carcinoma (HCC). In this review, we concentrate on several unexplored aspects of these phenomena, whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 80 publications
0
3
0
1
Order By: Relevance
“…The reason for this is both ultrastructural changes of myocytes and their atrophy, and changes in electrolyte homeostasis and bioelectric activity in general [ 44 ]. During the development of alcoholic myopathy, first of all, there is a hypergeneration of free radicals in dysfunctional mitochondria [ 45 , 46 ], which causes the destruction of the membrane structures of myocytes and functional disorders of their enzyme systems [ 47 ]: a decrease in the activity of Na + /K + -ATPase and an increase in ‒ Ca 2+ -ATPase. The miotic disorders cause an imbalance in the correction of the joints positioning and progressive muscle weakness, which leads to the degradation of muscle strength with 3, 6 and 9 months of alcoholization.…”
Section: Resultsmentioning
confidence: 99%
“…The reason for this is both ultrastructural changes of myocytes and their atrophy, and changes in electrolyte homeostasis and bioelectric activity in general [ 44 ]. During the development of alcoholic myopathy, first of all, there is a hypergeneration of free radicals in dysfunctional mitochondria [ 45 , 46 ], which causes the destruction of the membrane structures of myocytes and functional disorders of their enzyme systems [ 47 ]: a decrease in the activity of Na + /K + -ATPase and an increase in ‒ Ca 2+ -ATPase. The miotic disorders cause an imbalance in the correction of the joints positioning and progressive muscle weakness, which leads to the degradation of muscle strength with 3, 6 and 9 months of alcoholization.…”
Section: Resultsmentioning
confidence: 99%
“…Viral hepatitis and NASH are important causes of liver cancer development. Liver fibrosis due to viral hepatitis and NASH has been shown to be a risk factor for the development of hepatocellular carcinoma 49 51 . It has been suggested that ADAM12 is significantly associated with liver fibrosis 52 .…”
Section: Discussionmentioning
confidence: 99%
“…Известно, что на этапе прогрессирования хронических фиброзирующих процессов в печени ведущая патогенетическая роль принадлежит уже не этиологическим факторам [2,3], которые способны лишь усиливать и ускорять процесс необратимого повреждения печени, а развитию глубоких структурных и функциональных нарушений иммунной системы. Иммунная система, являясь одной из важнейших регуляторных систем организма (наряду с нервной и гуморальной), ответственна не только за поддержание иммунного гомеостаза, но и за регуляцию восстановительных регенераторных процессов [4−6], а также за реализацию защитно-приспособительных реакций организма, не связанных с иммунным ответом [7].…”
Section: Reviewunclassified